2021
DOI: 10.3390/nu13041084
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Shows Higher Sensitivity than Insulin to Grapeseed Proanthocyanidin Extract (GSPE) Treatment in Cafeteria-Fed Rats

Abstract: The endocrine pancreas plays a key role in metabolism. Procyanidins (GSPE) targets β-cells and glucagon-like peptide-1 (GLP-1)-producing cells; however, there is no information on the effects of GSPE on glucagon. We performed GSPE preventive treatments administered to Wistar rats before or at the same time as they were fed a cafeteria diet during 12 or 17 weeks. We then measured the pancreatic function and GLP-1 production. We found that glucagonemia remains modified by GSPE pre-treatment several weeks after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…2). This situation differs from the effects observed in young animals, 11 independently of the fed/fasted situation (unpublished results). GSPE PRE treatment showed different trends between aged and young animals.…”
Section: Ileum Enteroendocrine Cells Showed the Highest Sensitivity T...contrasting
confidence: 69%
See 2 more Smart Citations
“…2). This situation differs from the effects observed in young animals, 11 independently of the fed/fasted situation (unpublished results). GSPE PRE treatment showed different trends between aged and young animals.…”
Section: Ileum Enteroendocrine Cells Showed the Highest Sensitivity T...contrasting
confidence: 69%
“…These authors showed an attenuated anorectic effect of GLP-1 after this short cafeteria diet. 34 The GSPE treatment before the cafeteria diet was very effective in young rats, increasing ileum GLP-1 mRNA, together with GLP-1R, 10 as well as pancreas GLP-1R, 11 giving these animals a higher pancreatic sensitivity to GLP-1. However, we found a different situation in 21-month-old rats.…”
Section: Ileum Enteroendocrine Cells Showed the Highest Sensitivity T...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth noting that GSPE also had hypoglycemic and weight-reducing effects in healthy rats. The mechanisms of GSPE affecting metabolism may be affecting the function of pancreatic β-cells, preventing the effect of a high-fat diet on pancreatic insulin secretion, Frontiers in Pharmacology frontiersin.org regulating intestinal microflora, and upregulating intestinal GLP-1 receptor expression (Liu et al, 2020;Grau-Bové et al, 2021). Accumulating evidence has demonstrated that hyperglycemia, high ROS production, and mitochondrial dysfunction are implicated in the development of DKD (Brownlee, 2005;Reidy et al, 2014;Jha et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Atthe GIT, a dose of GSPE modulates enterohormone secretion, which has a satiating effect on food intake during treatment [24]. Treatment with GSPE improves the endocrine pancreas function and produces higher sensitivity to incretin hormones [25]. Moreover, some of these effects are maintained several months after the end of the treatment [26].…”
Section: Of 12mentioning
confidence: 99%